2008
DOI: 10.1007/s00464-008-9885-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of fibrin sealant to prevent major complications following laparoscopic gastric bypass: results of a multicenter, randomized trial

Abstract: The use of fibrin sealant in laparoscopic RYGBP may be beneficial in reducing the reintervention rate for major perioperative (<30 days) complications. Larger studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Although other studies have described the effectiveness of fibrin glue applied to anastomoses to prevent leakage [31][32][33]41], they give no information about the effect of applying Coseal to gastrointestinal anastomoses. In our study, the proximal anastomoses showed a similar resistance to pressure, regardless of the treatment used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other studies have described the effectiveness of fibrin glue applied to anastomoses to prevent leakage [31][32][33]41], they give no information about the effect of applying Coseal to gastrointestinal anastomoses. In our study, the proximal anastomoses showed a similar resistance to pressure, regardless of the treatment used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described the use of biological sealants to prevent anastomotic leakage in other types of surgery, such as laparoscopic gastric bypass [29] or cardiovascular surgery [30], but very few studies [31][32][33] are available on the role of biological sealants in the prevention of anastomotic leakage in colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized study on esophageal anastomoses in infants born with esophageal atresia, a significantly reduced incidence of anastomotic leakage and stricture was found in the group sealed with FG [85]. Two human studies on FG sealing of anastomoses in patients with Roux-en-Y gastric bypass found a nonsignificantly decreased incidence of anastomotic leakage in the sealing group [86,87]. Another human study on anastomotic leakage after laparoscopic resection of rectal cancer found a leakage rate of 5.8% in the FG-sealed group compared with 10.9% in the nonsealed group.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] Fibrin glue is being used in various pathologies including upper gastrointestinal tract perforations, [7,12] fistulas [13,14] and leaks. [15,16] DuraSeal, which is an absorbable synthetic hydrogel, has blue solution and limpid solution. DuraSeal is a newly introduced material aiming to minimize leaks in various organs, such as cerebrospinal fluid in neurosurgery, air in thoracic surgery and blood in vascular surgery.…”
Section: Resultsmentioning
confidence: 99%